Augmented Reality Improves Procedural Work on an International Space Station Science Instrument. (September 2019) - Braly, Adam M.; Nuernberger, Benjamin; Kim, So Young
Objective: The purpose of the current study was to determine whether an augmented reality instruction method would result in faster task completion times, lower mental workload, and fewer errors for simple tasks in an operational setting. Background: Prior research on procedural work that directly compared augmented reality instructions to traditional instruction methods (e.g., paper) showed that augmented reality instructions can enhance procedural work, but this was not true for simple tasks in an operational setting. Method: Participants completed simple procedural tasks on spaceflight hardware using an augmented reality instruction method and a paper instruction method. Results: Our results showed that the augmented reality instruction method resulted in faster task completion times and lower levels of mental and temporal demand compared with paper instructions. When participants used the augmented reality instruction method before the paper instruction method, there was a transfer of training that improved a subsequent procedure using the paper instruction method. Conclusion: An off-the-shelf augmented reality head-mounted display (HoloLens) can enhance procedural work for simple tasks in an operational setting. Application: The ability of augmented reality to enhance procedural work for simple tasks in an operational setting can help in reducing costs and mitigating risks that could ultimately lead to accidents and critical failures.